The Trending Technologies in the World of Precision Agriculture: A Systematic Literature Review - Bhanu Priyanka Valluri, Amandeep Sharma (International Journal of Advanced Science and Technology, 2020)
In any developing or developed country agriculture sector plays a pivotal role. To respond to the demographic challenge, there should be a growth in agriculture yield. The increase in population requires to meet the supply and demand ratio of food as a basic need. During this modernization era of the world, improvement in the latest technology in the field of agriculture can provide a better yield. Our recent technology helps to produce a better crop at the correct time which in turn results to achieve better productivity and economic growth of a country. Modernization in the agriculture sector is leading to the growth in both quantitative and qualitative productivity of farming by implementing the ideologies of different technologies. The technologies created a beneficial aid to the agriculture world called “smart agriculture” by providing a solution for achieving the aimed results. Smart framing is the a state-of-the-art technology that operates simply by taking basic inputs to feed from farmers according to their requirements which in turn and increase in growth in productivity with the help of techniques. In this process the farmers can analyses, monitor and track their yield productivity by the advancements in automation. The main animus of this review is to understand the present conditions, aids, and challenges in this sector. With the constant growth in the world of technologies, leads to the betterment of farmers. This motivated the concept of smart framing also known as “Precision Agriculture”. In total of 42 review articles are apprehend by following the PRISMA guideline to introspect the technicalities upheaval for distant components of precision agriculture. This article gives a summary of a few mostly used technologies in this sector based on their basic parameters, technologies, and implementation.